2020
DOI: 10.1104/pp.20.00485
|View full text |Cite
|
Sign up to set email alerts
|

The Tomato DELLA Protein PROCERA Promotes Abscisic Acid Responses in Guard Cells by Upregulating an Abscisic Acid Transporter

Abstract: The tomato DELLA protein PROCERA promoted abscisic acid-induced stomatal closure and gene expression by upregulating the expression of the ABA transporter ABA-IMPORTING TRANSPORTER 1 in guard cells. List of author contributions: H.S. performed most of the experiments. Y.K. performed transport assays in yeast. N.I-E. provided some of the materials used in this study, H.S, M.S. and D.W. designed the experiment and analyzed the experimental data. H.S., M.S. and D.W. wrote the manuscript.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…1b). Comparing transcript levels of all GA2oxs in isolated WT guard cells using available RNA‐seq data (Shohat et al ., 2020), revealed that GA2ox7 expression was much higher than all other GA2oxs (Fig. S2).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…1b). Comparing transcript levels of all GA2oxs in isolated WT guard cells using available RNA‐seq data (Shohat et al ., 2020), revealed that GA2ox7 expression was much higher than all other GA2oxs (Fig. S2).…”
Section: Resultsmentioning
confidence: 94%
“…A rapid and efficient guard‐cell isolation procedure (see methods in Shohat et al ., 2020) was used to examine if water deficiency affects GA accumulation in guard cells. This rapid procedure was taken to minimise the effect of the isolation process on transcription and hormone metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several ABA transporters have been identified so far. In Arabidopsis , ABCG40 imports ABA into guard cells ( 15 , 45 ), and in tomato, AIT1.1 was recently shown to play a role in ABA import into guard cells in an aspartic acid–glutamic acid–leucine–leucine–alanine (DELLA)–dependent manner ( 67 ). In addition, NPF4.6 regulates vasculature ABA import, and ABCG25 and DTX50 regulate vasculature ABA export ( 24 ).…”
Section: Discussionmentioning
confidence: 99%